Peristiwa Isra’ Mi’raj Nabi Muhammad SAW dalam Tinjauan Konsep Teleportasi dan Lintas Dimensi - Muhamad Nuryadin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
Abstract: In the Isra' Mi'raj event of the Great Prophet Muhammad SAW which occurred 14 centuries ago in the Arab Land, it invited many questions from various groups, both from scholars with a scientific approach, from religious circles based on the Shari'a from the Holy Book (Al-Qur'an), as well as among both (scholars as well as clergy), as well as among the general public by means of skepticism. So that the event can be accepted by all groups logically, this article will explain the explanation, both with a scientific approach through the theory of relativity (space-time-matter), as well as based on the Shari'a of the Qur'an, especially QS: An-Naml (27 ): 38 – 42 and QS: An-Nur (24): 35, and also uses the approach of analogies in the microscopic realm (atomic theory), namely: Bohr's atomic theory.